OP27 Factors associated with timely referral, diagnosis and treatment for lung cancer: cohort study using linked cancer registry, Hospital Episode Statistics, and audit data. (2nd September 2014) - Forrest, LF; White, M; Rubin, G; Adams, J
Abstract : Background: Early diagnosis of cancer is thought to be important for improving survival. Delays between the onset of cancer symptoms and receipt of treatment could result in potentially-resectable tumours becoming inoperable. In order to reduce delay, the NHS Cancer Plan set target waiting times for urgent cancer referral (14 days to first hospital appointment) and treatment (31 days from diagnosis [decision to treat], 62 days from urgent general practitioner [GP] referral). Interim diagnostic targets can be inferred. There is little definitive evidence on the factors that influence delay in lung cancer care. The aim of this study was to examine factors that may be important for timely referral, diagnosis and treatment within target for lung cancer, using linked cancer registry, Hospital Episode Statistics (HES) and lung cancer audit datasets. Methods: Data for 28, 733 lung cancer patients diagnosed in 2006–2010 were analysed. Logistic regression was used to investigate the factors (socio-economic position [SEP], age, sex, histology, co-morbidity, year of diagnosis, stage, and performance status [PS, a measure of patient health status]) that may influence timely referral, diagnosis and treatment, in mutually adjusted multivariable models. Co-morbidity data (n = 18, 650, 65%) were obtained from HES. Data on stage (n = 7769, 27%) and performance status (n = 8885, 31%) were obtained from audit data. Results: All patients had a date of diagnosis, 15, 452 (54%) had a GP referral date and 15, 373 (54%) received any treatment within one year of diagnosis. Late-stage, poor PS and small-cell histology were associated with a higher likelihood of referral, diagnosis and treatment within target. Older patients were significantly less likely to receive treatment within the 31 day target from diagnosis (OR=0.78, 95% CI 0.68 to 0.89) and within 62 days from GP referral (OR=0.77, 95% CI 0.65 to 0.91). Socio-economic inequalities were found in the time interval from GP referral to first hospital appointment. However, a linear trend was not seen. Patients in the middle SEP groups, but not the most deprived group, were less likely to have a first hospital appointment within 14 days, compared to the least deprived SEP group. Conclusion: Older patients waited longer for lung cancer treatment. Clinicians need to ensure that older patients do not undergo unnecessary and unjustified delays in treatment. Patients who appeared ill were referred more quickly and this 'sicker quicker' effect may cancel out system socio-economic inequalities that might result in longer time intervals for more deprived lung cancer patients.